Regulatory role of heat-shock proteins in autoimmune and inflammatory diseases - Daneri Becerra, Cristina del Rosario (2016)
Classically, molecular chaperones play a pivotal role in the maintenance of cellular proteostasis and thus, in the safeguarding of the cell homeostasis while reducing the deleterious effects of extracellular and intracellular stresses. They are also active players in immunologically relevant scenarios such as the activation of innate immunity, antitumour immunity, and autoimmune diseases. It is currently accepted that misdirected immune responses may target self-antigens and generate severe inflammatory responses, a typical signature of autoimmune diseases. In addition to numerous components in immune responses, chaperone proteins are also detected in the extracellular fluids and have been implicated in autoimmune and inflammatory diseases acting as pro- and anti-inflammatory factors. In several inflammatory pathologies, chaperones are greatly induced as a direct consequence of the inflammatory stress and are released from the cell thanks to a poorly understood mechanism. These extracellular chaperones are capable to stimulate anti-inflammatory regulatory T cell responses, thereby inducing the negative feedback control of inflammation. Therefore, it has been proposed that immunization with heat-shock protein peptides could prevent the development of certain diseases. In this article we review the basics of the stress response, summarize current controversies over the role of extracellular chaperones in inflammatory reactions and autoimmunity, and discuss the cytoprotective and immunoregulatory roles of heat-shock proteins, a challenging subject that may open a new avenue for the drug discovery and treatment of diseases related to autoimmune disturbs.